2009
DOI: 10.1016/j.rmed.2009.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of the efficacy of a pulmonary rehabilitation programme in patients with COPD

Abstract: Clinical and functional baseline findings do not predict the response to PRP in COPD. The greater efficacy in patients with BMI>25 or with PaO(2)<60mmHg may be due to a greater deconditioning in overweight patients, and to a larger room for improvement in hypoxemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
67
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 29 publications
12
67
4
2
Order By: Relevance
“…Similar results have been already demonstrated in a smaller group of patients taken from a real-life setting and submitted for outpatient rehabilitation [38]. Thus, these patients should not be definitively excluded from standard PR in the usual clinical setting.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results have been already demonstrated in a smaller group of patients taken from a real-life setting and submitted for outpatient rehabilitation [38]. Thus, these patients should not be definitively excluded from standard PR in the usual clinical setting.…”
Section: Discussionsupporting
confidence: 84%
“…Our finding that there were no significant changes between groups implies that PR yields clinical benefits for all groups. Some studies have suggested that patients with less severe obstruction have greater improvements in exercise tolerance [15], but this was not the case in our study.…”
Section: Discussioncontrasting
confidence: 88%
“…Regardless of the COPD-systemic inflammatory related nature of comorbidities, an intriguing issue is whether comorbidities may be related to the response to rehabilitation [7,25]. Recently, a retrospective cohort study examined this question.…”
mentioning
confidence: 99%